2015
DOI: 10.1117/12.2078883
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of liquid crystal device into THz phase imaging

Abstract: We investigate the terahertz (THz) phase imaging using liquid crystal (LC) device. Recently, there have been extensive efforts to measure the refractive indices and transmission losses of some LC materials in THz region. From these results, LC materials show relatively large refractive index anisotropy and they can have a potential application to some control devices similar to the display application. Furthermore, tunable LC THz phase shifter has been reported. In this study, an attempt was made to introduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…We previously reported that the birefringence of E44 is 0.2 [33]. The thickness of the LC layer was 800 μm in this case, and the retardation R of the E44 phase shifter was 160 μm.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…We previously reported that the birefringence of E44 is 0.2 [33]. The thickness of the LC layer was 800 μm in this case, and the retardation R of the E44 phase shifter was 160 μm.…”
Section: Resultssupporting
confidence: 50%
“…Here we also show the reported values of birefringence, absorption coefficients, and dielectric anisotropy for several LCs from References [8,12,22,32,33]. The birefringence of LC1 at 2.5 THz was We successfully observed the transmittance oscillation by increasing the applied voltage.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, PEDOT: PSS films can be easily fabricated by spin coating [12]. In a previous work, Ito et al [13] investigated THz phase imaging using an 800 µm thick homogeneous LC device using pristine PEDOT: PSS electrode layers and achieved a 360 • phase shift at 2.5 THz. More than 75 V of bias, however, was needed to achieve a 90 • phase shift.…”
Section: Introductionmentioning
confidence: 99%